Drawing and Ignoring: The Perception of the Pictorial Line. (August 2020) - Schott, G. D.
For over 2000 years, the pictorial line has been recognized as being fundamental to drawing and several other art forms. Yet pictorial lines present intriguing issues, three of which are considered here: lines very rarely exist in the natural world; there is no known part of the brain which "processes" lines; and, paradoxically, we often pay very little attention to the lines themselves, and they have even been viewed as "an imaginary idea".